Impact of leverage on shareholders' return: a study on selected listed manufacturing companies in sri lanka - Nirujah, R.; Niththiya, S.; Kunalan, J.; Visuvarajh, T.; Adams, M.V.; Kinchchili, T. (university of Jaffna, 2014)
This study is aimed to examine the impact of leverage on shareholders' return of selected listed manufacturing companies on Colombo stock exchange (CSE) in Sri Lanka. Leverage is the proportionate ratio of debt and shareholders' fund that influence the return of shareholders of a firm. No of researchers havebeen conducted over the years on these issues. The present study considered Leverage as the independent variable which measured by debt to equity(DE), debt to total asset(DTA) and shareholders' return as the dependent variable which measured by return on shareholders' fund (ROSF), earning per shares (EPS), and dividend yield(DY). The sample of this study has been examined the twelve manufacturing companies listed on CSE over a period of five years from 2008 to 2012. The required data and information for the study were gathered from published annual reports, fact book, and website of listed companies in CSE from 2008 to 2012. Correlation and regression analysis were used to find out the relationship and state the impact between leverage and shareholders' return. Analyzed results revealed that suggest there is a negative relationship between all variables other than debt to total asset and earnings per share.
Keywords: Leverage; Shareholders' return; Earnings